Komunikasi Interpersonal Mahasiswa dengan Perbedaan Budaya di Fakultas Ilmu Administrasi Universitas Brawijaya - Eka Valen Anggun Cahyani; Nurul Pringgowati; Arsih Amalia Chandra Permata (TUTURAN: Jurnal Ilmu Komunikasi, Sosial dan Humaniora, 2024)
The existence of cultural differences results in an individual or someone having to do interpersonal communication. In addition, through interpersonal communication is a way to connect these differences because of communication. The purpose of this study is to clarify the process, inhibiting factors, and effective interpersonal communication methods in bringing together cross-cultural languages. This research uses qualitative methods through observation, interviews, and documentation used to collect data. Qualitative data analysis is done through data reduction, data presentation, and conclusion drawing or validation. This research is used to explain things related to the process of interpersonal communication in the context of intercultural meetings at the Faculty of Administrative Sciences, Universitas Brawijaya.